PERBANDINGAN AKTIVITAS ANTIFUNGI EKSTRAK KULIT BUAH Citrus aurantifolia DAN Citrus hystrix DC SEDIAAN TUNGGAL DAN KOMBINASI TERHADAP Candida albicans - Nurwafa, Nurwafa; Budiarti, Lia Yulia; Khatimah3, Husnul (Universitas Lambung Mangkurat, 2023)
Candidiasis infection is often found in tropical area populations such as Indonesia with the main causative agent is Candida albicans (C.albicans). The peels of Citrus aurantifolia (C. aurantifolia) and Citrus hystrix DC (C. hystrix) contain several active compounds that can be used as alternative antifungals. This study aims to analyze the antifungal activity of C. aurantifolia and C. hystrix DC fruit peels extracts in single and combination forms in inhibiting the growth of C. albicans. This study method was a posttest-only with control group design, using the diffusion test method. The test treatments in 3 repetitions consisting of ethanol extracts from C.aurantifolia (Ca) and C. hystrix (Ch) fruit peels in single and combinations (Ca+Ch) concentrations at 25%, 50%, 75%, and 100%, the controls used ketoconazole and DMSO 1% . Analysis of inhibitory zone data as an antifungal effect on C.albicans ATCC 10231 using the One-way Anova test, Post Hoc Duncan test, and the independent T-test. The results showed that the difference in the inhibitory zone produced by the combination treatment effect greater than the single treatment (p<0.05), Ca100%+Ch100% treatment produced the widest inhibitory zone, which was 21.19 mm, and was not significantly different from ketoconazole. In conclusion, the combination of ethanol extract from C. aurantifolia and C. hystrix DC fruit peels produced a greater antifungal effect than either single preparation in inhibiting the growth of C. albicans.